TRAINING OF PENCAK ART TO PRESERVE LOCAL LIFE IN YOUTH ORGANIZATION KP. ANDIR RT. 01 RW. 15 VILLAGE PADALARANG, WEST BANDUNG DISTRICT - Edy Syafrudin; Sri Nurhayati (IKIP Siliwangi Bandung, 2020)
The background of the researchers conducting this research is that the art of pencak art is determined as an intangible cultural heritage by UNESCO so that it hopes that pencak art as an intangible cultural heritage. With this placement, it is expected that young people through youth can continue to cultural background and want to get involved in training conducted as provisions. This training is intended to be able to elevate the art of Pencak among the general public as well as to preserve local culture that has begun to be marginalized in this era of globalization.The purpose of this training is to find out about Pencak Art Training to Preserve Local Wisdom in Youth Organization Kp. Andir RT. 01 RW. 15 Padalarang Village, West Bandung Regency. The theory used in this research is the theory of youth, training theory and pencak art theory.Researchers conducted interviews and observation techniques with qualitative descriptive methods to obtain information from resource persons. The sample of this study was one trainer, 6 trainees, one Youth Organization Chairperson and one RW Kp Chairperson. Andir is chosen randomly.The results of the research on Pencak art training to preserve local wisdom in Youth Organization Kp. Andir kec. Padalarang, West Bandung regency is in line with expectations where the community in the village. Andir padalarang has begun to recognize and know the training of pencak arts. There were also many benefits felt by the participants.The conclusion of this study is Kp. Andir Padalarang to introduce pancak art in general society, especially young people so that Pencak art is not easily lost and is increasingly developing as our nation's cultural heritage in the midst of today's digitized world competition.